2020
DOI: 10.1534/g3.120.401521
|View full text |Cite
|
Sign up to set email alerts
|

Genome Resequencing, Improvement of Variant Calling, and Population Genomic Analyses Provide Insights into the Seedlessness in the GenusVitis

Abstract: The seedlessness of grape derived from stenospermocarpy is one of the most prized traits of table or raisin grapes. It is controlled by a complex genetic system containing one dominant gene and multiple recessive genes. Here, we collected dense variation data from high-depth resequencing data of seeded, seedless, and wild relative grape genomes sequenced to > 37x mean depth. Variant calls were made using a modified variant calling pipeline that was suitable for highly diverse interspecific grape accessions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Moreover, more recently QTLs studies have revealed the contribution of a region located on top of chromosome 1 including VviINO gene to the total seeds fresh weight (TSFW) per berry trait 44 , further supporting VviINO as a candidate for grapevine seedlessness. An association to seedlessness in this genomic part of Chr1 was also confirmed by resequencing of seedless and seeded varieties, even though no associated SNP located in this gene were found in the studied panel 10 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, more recently QTLs studies have revealed the contribution of a region located on top of chromosome 1 including VviINO gene to the total seeds fresh weight (TSFW) per berry trait 44 , further supporting VviINO as a candidate for grapevine seedlessness. An association to seedlessness in this genomic part of Chr1 was also confirmed by resequencing of seedless and seeded varieties, even though no associated SNP located in this gene were found in the studied panel 10 .…”
Section: Discussionmentioning
confidence: 53%
“… 4 , 5 for a summary). The Sultanine (or Thomson seedless) cultivar contributes to the SEED DEVELOPMENT INHIBITOR ( SDI ) locus, the major source of seedlessness exploited for breeding purposes and in commercial grapevine cultivars 6 – 10 . A recent study has elucidated the molecular basis of this trait demonstrating this is associated with a missense mutation in the MADS-Box gene VviAGL11 controlling seed coat development and lignification 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most used varieties to develop new genotypes 28 . As a seeded grape variety, it contains recessive loci for seedlessness 29 . Alternate drip irrigation of the Rizamat variety was shown to keep the same photosynthesis level but a lower transpiration rate 30 .…”
Section: Resultsmentioning
confidence: 99%
“…We explored the Vv SDR syntenic region between 5055465 and 5198824 on Amur grape chromosome 2, showing good synteny between two species. To determine whether the Amur grape putative SDR region is related to sex, we adopted the selective sweep method, which allows analysis of fewer samples than GWAS (Kim et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%